Changes and mechanisms of apparent resistivity before earthquakes of MS6.0–6.9 on the Chinese mainland - Xie, Tao; Han, Ying; Ye, Qing; Xue, Yan (Frontiers in Earth Science, 2023)
Since China carried out fixed continuous DC apparent resistivity observation in 1967 to June 2022, there have been 45 earthquakes with magnitude of MS6.0 6.9 occurred within a range of about 250 km around the monitoring stations which were in normal operation. As counted by stations, 61 middle-short term anomalous changes in apparent resistivity (i.e., 44 decline changes, 15 rise changes, and 2 perturbance changes) appeared before 39 of these earthquakes, through literature investigation and data analysis. In this paper, we use a fault virtual dislocation model to calculate the relative deformation characteristics around the epicenters before these earthquakes. The results show that 36 of the 44 decline changes were located at areas of compression enhancement. 9 of the 15 rise changes were located at areas of relative dilatancy. According to the results from experiments and resistivity model of cracked medium, the resistivity of water-bearing geomaterial presents decline changes during the successive loading of compressive stress while recovering rise changes during stress unloading. 45 of the 61 apparent resistivity anomalies are consistent with the mechanism of resistivity change under stress. These changes in apparent resistivity before earthquakes may be related to the seismogenic process through a way of resistivity changes caused by medium deformation.